Constitutional and legal references in the implementation of oversight over the constitutionality of laws: المرجعيات الدستورية والقانونية في إعمال الرقابة على دستورية القوانين - سعيد , الغازي (African Scientific Journal, 2020)
Abstract This study deals with the constitutional and legal references that adopted by the constitutional judge during his determination of the constitutionality of laws, in consideration that the constitution is the supreme law within the legal system of the political system, And the rest laws must be identical with it, to keep the constitutional rules and principles stipulated therein on the one hand, and to maintain its supreme on other hand. This congruence and consistency requires the existence of a constitutional and legal reference It is entrusted with overseeing the constitutionality of laws, protecting the rights and freedoms enshrined by the constitutional legislator through the constitutional document. The study reached several results, the most important of which is that the constitutional judge's references differ according to the nature of the political system and the foundations on which it is based, even if the goal is to protect the constitution, rights and freedoms, and to control the balance between the constitutional powers within the political system. The practice of the constitutional judiciary for its competencies is based on a set of references, including the constitutional document, the preamble of the constitution, regulation laws, principles and objectives that have constitutional value , in addition to the "judicial precedents" that produced by the constitutional judiciary in previous experiences. It also concludes from The jurisprudence of the constitutional judiciary that there is respect for the hierarchy of legal rules, so that the lower rule may not contradict the supreme rule, out of respect for the principle of the supremacy of the constitution over the rest of the laws, which forms the basis for overseeing the constitutionality of laws, and respect for the constitutional and legal legitimacy. Key words: Constitutional judiciary The control on the constitutionality of laws. References of the constitutional judge in control on the constitutionality of laws. الملخص تناولت هذه الدراسة المرجعيات الدستورية والقانونية المعتمدة من طرف القاضي الدستوري أثناء بته في دستورية القوانين، على اعتبار أن الدستور هو القانون األسمى داخل المنظومة القانونية للنظام السياسي، وأن باقي القوانين يجب أن تكون متطابقة معه، حفاظا على القواعد والمبادئ الدستورية المنصوص عليها فيه من جهة، وحفاظا على سموه من جهة ثانية، هذا التطابق والتناسق يقتضي وجود مرجعية دستورية وقانونية يناط بها أمر الرقابة على دستورية القوانين، حماية للحقوق والحريات التي كرسها المشرع الدستوري من خالل الوثيقة الدستورية. وتوصلت الدراسة لعدة نتائج أهمها أن مرجعيات القاضي الدستوري، تختلف حسب طبيعة النظام السياسي والمرتكزات التي ينبني عليها، وإن كان الهدف هو حماية الدستور والحقوق والحريات وضبط التوازن بين السلطات الدستورية داخل النظام السياسي. ممارسة القضاء الدستوري الختصاصاته، تستند على مجموعة من المرجعيات، منها الوثيقة الدستورية، مقدمة الدستور، القوانين التنظيمية، المبادئ واألهداف ذات القيمة الدستورية، اضافة إلى "السوابق القضائية" التي أنتجها القضاء الدستوري في التجارب السابقة. يستنتج كذلك من خالل اجتهادات القاضي الدستوري أن هناك احترام لتدرج القواعد القانونية، بحيث ال يجوز للقاعدة األدنى أن تخالف القاعدة األسمى، احتراما لمبدأ سمو الدستور على باقي القوانين، والذي يشكل أساس الرقابة على دستورية القوانين، واحتراما للشرعية الدستورية والقانونية. الكلمات المفتاحية: - القضاء الدستوري. - الرقابة على دستورية القوانين. - مرجعيات القاضي الدستوري في الرقابة على دستورية القوانين.